The Soviet theater : a documentary history - Senelick, Laurence; Ostrovsky, Sergei (Yale University Press, 2014)
In this monumental work, Laurence Senelick and Sergei Ostrovsky offer a panoramic history of Soviet theater from the Bolshevik Revolution to the eventual collapse of the USSR. Making use of more than eighty years' worth of archival documentation, the authors celebrate in words and pictures a vital, living art form that remained innovative and exciting, growing, adapting, and flourishing despite harsh, often illogical pressures inflicted upon its creators by a totalitarian government. It is the first comprehensive analysis of the subject ever to be published in the English language.